User awareness of and satisfaction with online subscriptions of the Aklatang Emilio Aguinaldo, De La Salle University Dasmariñas - Samaniego, Sharon M. (School of Library and Information Studies, University of the Philippines Diliman, 2009)
Libraries do not only provide their clientele with printed resources since there are available online subscriptions. This study was conceived in the light of the availability of these resources. Since libraries allocate a huge amount for access to online subscriptions, this study intended to find out the awareness and satisfaction of the Aklatang Emilio Aguinaldo's clientele specifically the students and faculty with the available online subscriptions which include e-journals.